Metáforas, metonímias e alegorias de um Brasil nas crônicas de Machado de Assis: o poder simbólico em História de quinze dias - Holanda, Antonio Euclides Vega de Pitombeira e Nogueira (2021)
This thesis studies the symbolic power and violence (BOURDIEU, 2001) in the cycle of chronicles História de quinze dias days and História de trinta dias, written under the pseudonym Manassés and published in the journal Illustração Brasileira between 1876 and 1878 by Machado de Assis. These two years are part of a period of national transition and host the latest productions before the “viravolta machadiana” (SCHWARZ, 2012). The watchful eye of the chronicler, who was constantly evolving as a writer, commented on his reality through subtle metaphors, metonyms, allegories, and silences, surpassing the direct and sometimes pamphleteering opinions of the early years. This transformation shows the paths that will be explored by the writer more vigorously from the 1880s onwards. The thesis analyzes the cycle of chronicles from the perception of power and violence relations which function as commentary and an aesthetic paradigm that can give meaning to texts (GINZBURG, 2012). In this manner, it allows for a description of the mentality and ideologies in nineteenth-century Brazil. The analysis of symbolic power in Machado's chronicles shows that the growing autonomy of the literary field (BOURDIEU, 1998) does not necessarily mean a distancing from the historical-social context. Studies on symbolic power (CASANOVA, 2008; SAPIRO, 2011), Machado's criticism (AZEVEDO, 2008; CARA, 2008; AMARAL, 2017) and the historical and social studies that follow the evolution of journalism in Brazil (CHALHOUB, 2003), especially in Rio de Janeiro, were the fundamentals of theoretical research that supported this thesis. Its main goal is to show how to describe symbolic violence based on elements of literature, even when the work has strong factual sediment, as is the chronicle as a genre. Furthermore, the thesis advances in Machado's studies by revealing a stage in the author's transformation processes, showing yet another thread in the web of mutual nourishment that his production had, alternating between genres as experiences and supports for ideas and reflections. The cycle of chronicles is unveiled, casting more light on the aesthetic transition and on the elements that make up Machado's production. In both cases, the thesis shows how the author writes through a system of symbols and shadows, with each change and break a piece in the coherent message, focused on the reflection of his time.